‘It is me who eats, to nourish him’: a mixed‐method study of breastfeeding in post‐earthquake Haiti - Jenny Dörnemann; Ann H. Kelly (Maternal and Child Nutrition)
Abstract In Haiti, initiation of breastfeeding is high, but early mixed feeding is the norm. In a situation of crisis, mothers' worries about insufficiency of breast milk, disruption of social networks and free unmonitored distribution of breast milk substitutes impact feeding practices. This study was conducted to explore the attitudes, practices and understandings of breastfeeding in the post‐earthquake situation in Haiti. A mixed‐method study was conducted in Léogâne, Haiti, a town close to the epicentre of the 2010 earthquake. In a household survey, 1131 mothers of children under 24 months were interviewed about feeding practices. In the quantitative component, we conducted 25 in‐depth interviews and seven focus group discussions with mothers, grandmothers, traditional birth attendants, fathers and health care professionals. Mothers described breastfeeding as a challenging responsibility to ensure the infants' health. They understood breast milk as a dynamic substance, the quality of which would deteriorate if the mother's diet was poor or if the mother was afflicted with a psychosocial condition called move san or colere, ‘bad blood’. To protect the child in these situations, early supplementary feeding is introduced. Only 20% of informants exclusively breastfed infants under 6 months. Because of a lack of confidence in the quality of breast milk, Haitian mothers tend to wean children earlier. The abiding concerns of Haitian mothers over the quality of their breast milk suggest a number of ways – such as dietary advice – that post‐earthquake aid agencies could enhance breastfeeding support.